Implementation of Budget Accountability to Measure Private University Financial Performance - Arun, Bahrun; Kholmi, Masiyah (Penerbit Goodwood, 2026)
Purpose: This study explores how budget accountability is implemented as a performance measurement tool in financial management at a private higher education institution in Baubau City, Southeast Sulawesi, Indonesia. It examines factors that support or hinder the process and their relation to institutional performance. Methodology/Approach: A qualitative case study approach was used at a private Islamic university. Data collection included in-depth interviews with six financial management staff, document analysis of budget plans and financial reports, and field observation. Data were analyzed using Miles and Huberman’s interactive model. The study applied theories of public accountability, organizational performance, and good governance. Results/Findings: The study found that budget accountability is implemented through formal planning, execution, and reporting processes. However, it is largely administrative with limited use of performance indicators. Supporting factors include leadership commitment, digital financial systems, and an open organizational culture. Challenges include limited staff capacity, rigid bureaucracy, and the absence of outcome-based performance metrics. Some units have aligned budgets with outputs, but efforts are inconsistent. Conclusions: Budget accountability practices in private universities are predominantly administrative. To improve performance measurement, enhancing leadership commitment, optimizing digital systems, and fostering a participatory organizational culture are crucial. Limitations: This study is limited to one private university in Baubau City, Southeast Sulawesi, with no comparative analysis across institutions or regions, limiting the generalizability of the findings. Contributions: This study enhances understanding of budget accountability in Indonesian private higher education and provides practical recommendations for institutional leaders, contributing to the discourse on financial governance in education.